Slick water fracturing fluid as well as preparation method and application thereof
By using chitosan, polymer matrix, paraformaldehyde and solvent in the slippery water fracturing fluid, a multiple network structure is formed, which solves the problems of low viscosity and high preparation cost of existing slippery water fracturing fluid, and achieves efficient sand carrying and salt resistance, which is suitable for high temperature and high mineralization environments.
Patent Information
- Application Number
- CN202311425845.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-30
- Publication Date
- 2025-05-02
AI Technical Summary
The existing slippery water fracturing fluid has low viscosity, difficulty in online mixing and high preparation cost, making it difficult to maintain effective sand carrying performance under high temperature and high mineralization environments.
Using a slippery water fracturing liquid including chitosan, polymer matrix, paraformaldehyde and solvent, through physical interpenetration and chemical crosslinking of the polymer main chain, combined with the coordination crosslinking of chitosan and molybdenum disulfide, a multiple network structure is formed to improve viscosity and salt resistance.
It realizes a slippery water fracturing fluid with high viscosity, easy to mix online and low cost, which can maintain good sand carrying performance under high temperature and high mineralization conditions, and improves the efficiency of oil and gas field development.
Smart Images

Figure CN119912930A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fracturing fluids, and in particular to a slick water fracturing fluid, a preparation method thereof and applications thereof. Background Art
[0002] Fracturing technology is one of the essential and important measures for the development of unconventional oil and gas in my country. It plays an important role in increasing production and reserve utilization. Fracturing fluid plays a very important role in fracturing, especially in carrying sand and creating fractures. In recent years, slickwater fracturing fluid has gradually attracted attention due to its excellent performance such as drag reduction. However, conventional slickwater fracturing fluid has low viscosity, weak sand carrying capacity, and small fracturing radius. Although slickwater fracturing fluid usually uses large liquid volume and large displacement. However, high-speed pumping not only causes large energy loss, but also places high requirements on ground pumping equipment. In addition, the dissolved salts and hardness components in the on-site return water are difficult to remove. Conventional slickwater fracturing fluid has low viscosity in brine, and its sand carrying performance is not good. At the same time, the temperature of the reservoir also has a certain impact on its effect.
[0003] In response to the above problems of conventional slickwater fracturing fluids, people began to study high-viscosity slickwater fracturing fluids, focusing on three aspects: (1) The sand-carrying mechanism of high-viscosity slickwater fracturing fluids: Field tests from the Anadarko Basin showed that viscosity is not the only determinant of the sand-carrying performance of high-viscosity slickwater fracturing fluids. Elasticity is usually an important factor that is overlooked and may have a significant impact on the sand-carrying performance; (2) Salt-tolerant high-viscosity slickwater fracturing fluids: In the Marcellus reservoir fracturing, the total mineralization of the produced water is 30,000 to 50,000. Laboratory tests show that the viscosity of high-viscosity slickwater fracturing fluids in clean water and produced water is 45 mPa·s, respectively. -1 and 12mPa·s -1 Salt has a great influence on the performance of slickwater fracturing fluid, so it is necessary to develop a salt-resistant high-viscosity slickwater fracturing fluid system; (3) Study on temperature sensitivity of high-viscosity slickwater fracturing fluid: The current laboratory evaluation temperature is 21°C to 82°C, and the upper limit of field use temperature is 168°C, which leads to a serious disconnect between the field and the indoor environment; Bageri et al. found that when the temperature of high-viscosity slickwater fracturing fluid increases from 25°C to 80°C, its viscosity increases from 33mPa·s -1 Reduced to 13mPa·s -1 ; At higher temperatures, the viscosity may drop further. How to prepare slick water fracturing fluid that can effectively carry sand at reservoir temperature still requires more research.
[0004] In order to solve the above problems, hydrophobic associating polymers are currently usually used to achieve high-viscosity slippery water fracturing fluids. However, when the concentration of hydrophobic associating polymers is high, they have strong hydrophobic associating effects and are difficult to dissolve in water. They are not easy to prepare as emulsions and can only exist in powder form. They are difficult to mix online and difficult to dissolve instantly. There are also problems such as high cost.
[0005] Therefore, it is of great significance to study and develop a slickwater fracturing fluid with high viscosity, easy online mixing and low cost. Summary of the invention
[0006] The main purpose of the present invention is to provide a slick water fracturing fluid, a preparation method and application thereof, so as to solve the problems of low viscosity, difficult online mixing and high preparation cost of slick water fracturing fluid in the prior art.
[0007] In order to achieve the above objectives, the present invention provides a slippery water fracturing fluid, which comprises chitosan, a polymer matrix, paraformaldehyde and a solvent; the polymer matrix is polyacrylamide and / or a hydrolyzate of polyacrylamide.
[0008] Furthermore, the slick water fracturing fluid comprises, in terms of weight percentage of the slick water fracturing fluid, 0.01-2.0 wt % chitosan, 0.01-2.0 wt % polymer matrix, 0.04-0.06 wt % paraformaldehyde and 2-4 wt % solvent.
[0009] Furthermore, the slick water fracturing fluid further comprises molybdenum disulfide; preferably, the slick water fracturing fluid further comprises 0.15-0.25 wt % of molybdenum disulfide, based on the weight percentage of the slick water fracturing fluid.
[0010] Furthermore, the relative molecular weight of chitosan is 50,000 to 600,000, preferably 100,000 to 400,000; and / or the relative molecular weight of polyacrylamide is 5 million to 15 million, preferably 7 million to 10 million; and / or the relative molecular weight of the hydrolyzate of polyacrylamide is 6 million to 9 million, and the molar ratio of amide group to carboxyl group is (98-70):(2-30); preferably, the molar ratio of amide group to carboxyl group is (98-70):(10-20); the degree of polymerization of paraformaldehyde is 8-10.
[0011] Further, the solid content of the slick water fracturing fluid is 30-40%; and / or the solvent is selected from one or more of the group consisting of water, brine and an acid solution with a molar concentration of ≤0.1 mol / L.
[0012] Furthermore, molybdenum disulfide has a 1T phase lamellar structure; preferably, the interlayer spacing of molybdenum disulfide is 0.5-0.7 nm, and the size is (10-100) nm×(1-20) nm, and more preferably (21-36) nm×(5-10) nm.
[0013] Furthermore, molybdenum disulfide is prepared by a lithium intercalation method or a hydrothermal method.
[0014] Furthermore, the slick water fracturing fluid comprises, in terms of weight percentage of the slick water fracturing fluid, 0.08-0.12 wt % chitosan, 0.5-0.7 wt % polyacrylamide hydrolysate, 0.04-0.06 wt % paraformaldehyde, 0.15-0.25 wt % molybdenum disulfide and the remainder water, and the molar ratio of amide group to carboxyl group in the polyacrylamide hydrolysate is (98-70):(10-20).
[0015] In order to achieve the above-mentioned purpose, another aspect of the present invention further provides a method for preparing the above-mentioned slick water fracturing fluid provided in the present application, the preparation method comprising: sequentially mixing chitosan, a polymer matrix, paraformaldehyde, optional molybdenum disulfide and a solvent to obtain a slick water fracturing fluid; preferably, hydrochloric acid is added during the mixing process of chitosan and the solvent to adjust the pH to 2-7.
[0016] Another aspect of the present invention provides an application of the above-mentioned slick water fracturing fluid provided in the present application, or the slick water fracturing fluid prepared by the preparation method of the above-mentioned slick water fracturing fluid provided in the present application in the field of oil and gas field development.
[0017] By applying the technical solution of the present invention, in the above-mentioned slick water fracturing fluid provided by the present application, chitosan and polymer are fully dissolved, and physical interpenetration and entanglement occur between the two polymer main chains. In the presence of paraformaldehyde, the polymer main chain is chemically cross-linked with it to form a primary network structure. Chitosan can form coordination cross-linking sites with molybdenum disulfide to obtain a secondary network structure, thereby forming a multiple network structure that cannot be separated and has a high viscosity; and the above-mentioned components have good solubility in the solvent, are easy to mix online, and have a low preparation cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0019] Figure 1 The cryo-electron microscopy image of sample 3 prepared in Example 3 of the present application is shown;
[0020] Figure 2 The viscosity performance test curves of samples 1 to 7 prepared in Examples 1 to 7 of the present application are shown;
[0021] Figure 3 The viscosities of samples 1 to 7 prepared in Examples 1 to 7 of the present application under different temperature conditions are shown;
[0022] Figure 4 The viscosity of samples 1 to 7 prepared in Examples 1 to 7 of the present application under water conditions with different mineralization degrees is shown. DETAILED DESCRIPTION
[0023] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0024] As described in the background art, the existing slick water fracturing fluid has the problems of low viscosity, difficulty in online mixing and high preparation cost. In order to solve the above technical problems, the present application provides a slick water fracturing fluid, which includes: chitosan, a polymer matrix, paraformaldehyde and a solvent.
[0025] In the above-mentioned slick water fracturing fluid provided by the present application, chitosan and polymer are fully dissolved, and physical interpenetration and entanglement occur between the two polymer main chains. In the presence of paraformaldehyde, the polymer main chain is chemically cross-linked with it to form a primary network structure. Chitosan can form coordination cross-linking sites with molybdenum disulfide to obtain a secondary network structure, thereby forming an indivisible multiple network structure with a high viscosity; and the above-mentioned components have good solubility in the solvent, are easy to mix online, and have a low preparation cost.
[0026] In a preferred embodiment, the slick water fracturing fluid comprises 0.01-2.0 wt% chitosan, 0.01-2.0 wt% polymer matrix, 0.04-0.06 wt% paraformaldehyde and 2-4 wt% solvent in terms of weight percentage of the slick water fracturing fluid. The weight percentage of each component in the slick water fracturing fluid includes but is not limited to the above range, and limiting it within the above range is beneficial to improving the degree of chemical crosslinking, thereby improving the viscosity of the slick water fracturing fluid; at the same time, it is beneficial to the dispersibility of each component in the solvent.
[0027] In a preferred embodiment, the slick water fracturing fluid also includes molybdenum disulfide. The introduction of molybdenum disulfide in the slick water fracturing fluid is conducive to forming coordinated reversible cross-linking sites in the polymer matrix, which is conducive to improving the degree of cross-linking, thereby helping to improve the temperature resistance of the slick water fracturing fluid; at the same time, it is conducive to improving the strength of the multiple network structure in the slick water fracturing fluid, and it is not easy to curl up when encountering salt water, which is conducive to improving the salt resistance of the slick water fracturing fluid.
[0028] In order to further improve the degree of cross-linking and the temperature and salt resistance of the slick water fracturing fluid, preferably, the slick water fracturing fluid further includes 0.15-0.25 wt % of molybdenum disulfide, based on the weight percentage of the slick water fracturing fluid.
[0029] In a preferred embodiment, the relative molecular weight of chitosan is 50,000 to 600,000, preferably 100,000 to 400,000. The molecular weight of chitosan includes but is not limited to the above range, and limiting it within the above range is conducive to improving the degree of chemical crosslinking, thereby improving the stability of the multiple network structure, and thus helping to increase the viscosity of the slick water fracturing fluid.
[0030] In a preferred embodiment, the relative molecular weight of polyacrylamide is 5 million to 15 million, preferably 7 million to 10 million. The molecular weight of polyacrylamide includes but is not limited to the above range, and limiting it within the above range is conducive to improving the degree of chemical crosslinking, thereby improving the stability of the multiple network structure, and thus helping to increase the viscosity of the slick water fracturing fluid.
[0031] In a preferred embodiment, the relative molecular weight of the polyacrylamide hydrolyzate is 6 to 9 million, and the molar ratio of the amide group to the carboxyl group is (98 to 70): (2 to 30). The molecular weight of the polyacrylamide hydrolyzate and its degree of hydrolysis include but are not limited to the above ranges, and limiting them within the above ranges is conducive to improving the degree of chemical crosslinking, thereby improving the stability of the multiple network structure, and thus helping to increase the viscosity of the slick water fracturing fluid.
[0032] In a preferred embodiment, the degree of polymerization of the paraformaldehyde is 8 to 10. The degree of polymerization of the paraformaldehyde includes but is not limited to the above range, and limiting it within the above range is conducive to improving the degree of chemical crosslinking, thereby improving the stability of the multiple network structure, and thus helping to increase the viscosity of the slick water fracturing fluid.
[0033] In a preferred embodiment, the solid content of the slick water fracturing fluid is 30-40%. The solid content of the slick water fracturing fluid includes but is not limited to the above range, which is conducive to giving full play to the advantages of the multiple network structure and improving the comprehensive performance of the slick water fracturing fluid.
[0034] In a preferred embodiment, the solvent includes but is not limited to one or more of the group consisting of water, brine and an acid solution with a molar concentration of ≤0.1 mol / L. The solvent includes but is not limited to the above range, and limiting it to the above range is conducive to improving the dispersibility of chitosan, polymer matrix and polyformaldehyde in the slick water fracturing fluid, thereby helping to improve the comprehensive performance of the slick water fracturing fluid.
[0035] In a preferred embodiment, molybdenum disulfide has a 1T phase lamellar structure. Molybdenum disulfide with a 1T phase lamellar structure has better conductivity and hydrophilicity than 2H phase molybdenum disulfide (2H type molybdenum disulfide is insoluble in water), and has a smaller size and higher activity. The structural difference between the two is mainly that the molybdenum disulfide with a 1T phase lamellar structure has a regular octahedral structure.
[0036] In order to further improve the temperature and salt resistance of the slick water fracturing fluid, preferably, the interlayer spacing of molybdenum disulfide is 0.5-0.7 nm, and the size is (10-100) nm×(1-20) nm, more preferably (21-36) nm×(5-10) nm.
[0037] In a preferred embodiment, molybdenum disulfide is prepared by lithium intercalation or hydrothermal method. Molybdenum disulfide can be prepared by a common method in the art. The molybdenum disulfide used in this application is prepared by a method described in the existing literature (Zhu Jingchun. Preparation and Research Progress of Molybdenum Disulfide Nanosheets [J]. Science and Technology Innovation, 2018.).
[0038] In a preferred embodiment, the slick water fracturing fluid comprises 0.08-0.12 wt% chitosan, 0.5-0.7 wt% polyacrylamide hydrolysate, 0.04-0.06 wt% paraformaldehyde, 0.15-0.25 wt% molybdenum disulfide and the balance water, and the molar ratio of amide group to carboxyl group in the polyacrylamide hydrolysate is (98-70):(10-20). Compared with other ranges, limiting the amount of chitosan, polyacrylamide hydrolysate, paraformaldehyde, molybdenum disulfide and water to the above range is beneficial to improving the viscosity of the slick water fracturing fluid, and at the same time, it is beneficial to improve the solubility and dispersibility of the above components in the solvent, which is beneficial to online mixing and reducing the preparation cost.
[0039] The second aspect of the present application also provides a method for preparing the above-mentioned slick water fracturing fluid provided by the present application, the preparation method comprising: sequentially mixing chitosan, a polymer matrix, paraformaldehyde, optional molybdenum disulfide and a solvent to obtain a slick water fracturing fluid. The preparation method of the above-mentioned slick water fracturing fluid provided by the present application is simple in process, easy to mix online, and has a low preparation cost.
[0040] In order to improve the dispersibility of chitosan in the solvent, preferably, hydrochloric acid is added during the mixing of chitosan and the solvent to adjust the pH to 2-7.
[0041] The third aspect of the present application also provides an application of the above-mentioned slick water fracturing fluid provided by the present application, or the slick water fracturing fluid prepared by the preparation method of the above-mentioned slick water fracturing fluid provided by the present application in the field of oil and gas field development. The above-mentioned slick water fracturing fluid provided by the present application has a high viscosity, and each component has good solubility in the solvent, so that it has good stability. When applied to the field of oil and gas field development, it can improve the oil and gas field production efficiency and achieve the performance of wetting reversal (i.e., from oleophilic to hydrophilic), and has a significant viscosity-enhancing effect, an increased sand carrying capacity, and a complex fracture network produced by fracturing, which can form a good oil and gas diversion channel.
[0042] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0043] It should be noted that the molybdenum disulfide used in this application is prepared by lithium ion intercalation or hydrothermal method. Among them, (1) lithium ion intercalation method: n-butyl lithium or tert-butyl lithium is often used as an intercalation agent, inserted into the conventional MoS2 sheet structure, increasing the van der Waals force between layers, and then exfoliated by ultrasonic hydrolysis to obtain MoS2 layered nanosheets; (2) hydrothermal method: the hydrothermal method uses water as a solvent, adds molybdenum source MoO3, reducing agent thiourea, and thioacetamide in a high-pressure reactor, and reduces to molybdenum disulfide nanosheets in a high-temperature (200°C) and high-pressure environment. The two methods synthesize 1T metallic phase and water-soluble molybdenum disulfide nanosheets (Zhu Jingchun. Preparation and research progress of molybdenum disulfide nanosheets [J]. Science and Technology Innovation, 2018.).
[0044] Example 1
[0045] A method for preparing a slick water fracturing fluid comprises:
[0046] 0.10 parts by weight of chitosan was mixed with 100 parts by weight of water to obtain a mixed system, the pH was adjusted to 5 with 0.1 mol / L hydrochloric acid, and then 0.1 parts by weight of polyacrylamide hydrolysate, 0.05 parts by weight of paraformaldehyde, and 0.2 parts by weight of molybdenum disulfide were added in sequence to obtain a slippery water fracturing fluid (referred to as sample 1). Among them, the molecular weight of chitosan is 300,000, the molecular weight of polyacrylamide is 8 million, and the molar ratio of amide group to carboxyl group in the polyacrylamide hydrolysate is 4:1, the degree of polymerization of paraformaldehyde is 9, and molybdenum disulfide has a 1T phase lamellar structure, the interlayer spacing is 0.65 nm, and the size is 35 nm×7 nm.
[0047] The slick water fracturing fluid comprises, in terms of weight percentage of the slick water fracturing fluid, 0.10 wt% chitosan, 0.1 wt% polyacrylamide hydrolyzate, 0.05 wt% paraformaldehyde, 0.2 wt% molybdenum disulfide and 99.55 wt% water. The solid content of the slick water fracturing fluid is 35%.
[0048] Example 2
[0049] The difference from Example 1 is that the weight percentage of the polyacrylamide hydrolyzate is 0.3 wt %. The amounts of chitosan, paraformaldehyde and molybdenum disulfide are the same as those in Example 1. The total weight of the prepared slick water fracturing fluid (referred to as Sample 2) is 100 parts, with the remainder being water.
[0050] Example 3
[0051] The difference from Example 1 is that the weight percentage of the polyacrylamide hydrolyzate is 0.6 wt %. The amounts of chitosan, paraformaldehyde and molybdenum disulfide are the same as those in Example 1. The total weight of the prepared slick water fracturing fluid (recorded as Sample 3) is 100 parts, with the remainder being water.
[0052] The cryo-EM scanning image of sample 3 is shown in Figure 1 As shown in the figure, it is shaped like hair, crisscrossed and formed into a net, with holes in the middle.
[0053] Example 4
[0054] The difference from Example 1 is that the weight percentage of the polyacrylamide hydrolyzate is 0.8 wt %. The amounts of chitosan, paraformaldehyde and molybdenum disulfide are the same as those in Example 1. The total weight of the prepared slick water fracturing fluid (referred to as Sample 4) is 100 parts, with the remainder being water.
[0055] Example 5
[0056] The difference from Example 1 is that the weight percentage of the polyacrylamide hydrolyzate is 0.1wt%, and the molar ratio of amide group to carboxyl group in the polyacrylamide hydrolyzate is 98:2. The amounts of chitosan, paraformaldehyde and molybdenum disulfide are the same as those in Example 1. The total weight of the prepared slick water fracturing fluid (referred to as Sample 5) is 100 parts, with the remainder being water.
[0057] Example 6
[0058] The difference from Example 1 is that the weight percentage of chitosan is 0.20wt%, the weight percentage of polyacrylamide hydrolyzate is 0.3wt%, and the molar ratio of amide group to carboxyl group in the polyacrylamide hydrolyzate is 70:30. The amount of paraformaldehyde and molybdenum disulfide is the same as that in Example 1. The total weight of the prepared slick water fracturing fluid (referred to as Sample 6) is 100 parts, and the balance is water.
[0059] Example 7
[0060] The difference from Example 1 is that the weight percentage of chitosan is 0.50wt%, the weight percentage of polyacrylamide hydrolyzate is 0.3wt%, and the molar ratio of amide group to carboxyl group in the polyacrylamide hydrolyzate is 50:50. The amount of paraformaldehyde and molybdenum disulfide is the same as that in Example 1. The total weight of the prepared slick water fracturing fluid (referred to as Sample 7) is 100 parts, and the balance is water.
[0061] Example 8
[0062] The difference from Example 1 is that the molecular weight of chitosan is 100,000, the relative molecular weight of the polyacrylamide hydrolyzate is 7 million, and the degree of polymerization of paraformaldehyde is 10.
[0063] Example 9
[0064] The difference from Example 1 is that the molecular weight of chitosan is 400,000, the relative molecular weight of the polyacrylamide hydrolyzate is 10 million, and the degree of polymerization of paraformaldehyde is 8.
[0065] Example 10
[0066] The difference from Example 1 is that the molecular weight of chitosan is 500,000, the relative molecular weight of the polyacrylamide hydrolyzate is 12 million, and the degree of polymerization of paraformaldehyde is 10.
[0067] Embodiment 11
[0068] The difference from Example 1 is that the molar ratio of amide group to amino group in the polyacrylamide hydrolyzate is 70:30.
[0069] Example 12
[0070] The difference from Example 1 is that the molar ratio of amide group to amino group in the polyacrylamide hydrolyzate is 98:2.
[0071] Embodiment 13
[0072] The difference from Example 1 is that the molar ratio of amide group to amino group in the polyacrylamide hydrolyzate is 50:50.
[0073] Embodiment 14
[0074] The difference from Example 1 is that the interlayer spacing of molybdenum disulfide is 0.5 nm and the size is 10 nm×7 nm.
[0075] Embodiment 15
[0076] The difference from Example 1 is that the interlayer spacing of molybdenum disulfide is 0.7 nm and the size is 100 nm×7 nm.
[0077] Example 16
[0078] The difference from Example 1 is that the interlayer spacing of molybdenum disulfide is 0.65 nm and the size is 400 nm×40 nm.
[0079] Embodiment 17
[0080] The difference from Example 1 is that the pH of the mixed system is adjusted to 2.
[0081] Embodiment 18
[0082] The difference from Example 1 is that the pH of the mixed system is adjusted to 7.
[0083] Embodiment 19
[0084] The difference from Example 1 is that the pH of the mixed system is adjusted to 10.
[0085] Embodiment 20
[0086] The difference from Example 1 is that polyacrylamide is added instead of polyacrylamide hydrolyzate during the preparation process.
[0087] Comparative Example 1
[0088] The difference from Example 1 is that no paraformaldehyde is added during the preparation process.
[0089] Comparative Example 2
[0090] The difference from Example 1 is that no polyacrylamide hydrolyzate is added during the preparation process.
[0091] Comparative Example 3
[0092] The difference from Example 1 is that no chitosan is added during the preparation process.
[0093] The viscosity test of the slick water fracturing fluids prepared in all the above examples and comparative examples of the present application was carried out, wherein the viscosity performance test curves of samples 1 to 7 prepared in Examples 1 to 7 are as follows: Figure 2 shown.
[0094] The viscosity properties of sample 3 prepared in Example 3 were tested at 20°C, 30°C, 40°C, 50°C, 60°C, 70°C and 80°C. The test results are as follows: Figure 3 shown.
[0095] In water with different mineralization degrees (Ca 2+ The viscosity of the sample 3 prepared in Example 3 of the present application was tested under the conditions of 500ppm, 1000ppm, 1500ppm and 2000ppm respectively. The test results are as follows Figure 4 As shown (the shear rate was set to 170.3s during the test -1 ).
[0096] The viscosity test results of the slick water fracturing fluids prepared in all the above examples and comparative examples of the present application are summarized in Table 1.
[0097] Table 1
[0098] <![CDATA[Viscosity (30 °C, mPa·s 1 )]]> <![CDATA[Viscosity (at 30 °C, 500 ppm Ca 2+ content in mineralized water, mPa·s 1 )]]> Example 1 12.5 5.1 Example 2 22.5 7.5 Example 3 60.0 20.0 Example 4 57.0 18.6 Example 5 27.0 9.6 Example 6 38.5 12.8 Example 7 18.0 7.2 Example 8 12.8 4.3 Example 9 12.3 4.1 Example 10 9.6 3.2 Embodiment 11 13.2 4.4 Example 12 12.8 4.3 Embodiment 13 8.1 2.7 Embodiment 14 12.5 4.2 Embodiment 15 13.2 4.4 Example 16 9.0 3.0 Embodiment 17 12.3 4.1 Embodiment 18 12.8 4.3 Embodiment 19 8.4 2.8 Embodiment 20 15.0 5.0 Comparative Example 1 5.0 1.7 Comparative Example 2 5.5 1.8 Comparative Example 3 5.0 1.7
[0099] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects: in the above-mentioned slick water fracturing fluid provided by the present application, chitosan and polymer are fully dissolved, and physical interpenetration and entanglement occur between the two polymer main chains; in the presence of polyformaldehyde, the polymer main chain is chemically cross-linked with it to form a primary network structure; chitosan can form coordination cross-linking sites with molybdenum disulfide to obtain a secondary network structure, and then form an indivisible multiple network structure with a higher viscosity; and the above-mentioned components have good solubility in the solvent, are easy to mix online, and have a low preparation cost.
[0100] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.
[0101] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A slick water fracturing fluid, characterized in that: The slick water fracturing fluid comprises: chitosan, a polymer matrix, paraformaldehyde and a solvent; the polymer matrix is polyacrylamide and / or a hydrolyzate of polyacrylamide.
2. The slick water fracturing fluid according to claim 1, characterized in that: Calculated by weight percentage of the slick water fracturing fluid, the slick water fracturing fluid comprises 0.01-2.0 wt % of the chitosan, 0.01-2.0 wt % of the polymer matrix, 0.04-0.06 wt % of the paraformaldehyde and 2-4 wt % of the solvent.
3. The slick water fracturing fluid according to claim 1 or 2, characterized in that: The slickwater fracturing fluid also includes molybdenum disulfide; Preferably, the slick water fracturing fluid further comprises 0.15-0.25 wt % of the molybdenum disulfide, based on the weight percentage of the slick water fracturing fluid.
4. The slick water fracturing fluid according to any one of claims 1 to 3, characterized in that: The relative molecular weight of the chitosan is 50,000 to 600,000, preferably 100,000 to 400,000; and / or, The relative molecular weight of the polyacrylamide is 5 million to 15 million, preferably 7 million to 10 million; and / or, The relative molecular weight of the polyacrylamide hydrolyzate is 6 to 9 million, and the molar ratio of the amide group to the carboxyl group is (98 to 70): (2 to 30); preferably, the molar ratio of the amide group to the carboxyl group is (98 to 70): (10 to 20); The polymerization degree of the paraformaldehyde is 8-10.
5. The slick water fracturing fluid according to claim 4, characterized in that: The solid content of the slick water fracturing fluid is 30-40%; and / or the solvent is selected from one or more of the group consisting of water, brine and an acid solution with a molar concentration of ≤0.1 mol / L.
6. The slick water fracturing fluid according to claim 3, characterized in that: The molybdenum disulfide has a 1T phase lamellar structure; Preferably, the interlayer spacing of the molybdenum disulfide is 0.5-0.7 nm, and the size is (10-100) nm×(1-20) nm, more preferably (21-36) nm×(5-10) nm.
7. The slick water fracturing fluid according to claim 6, characterized in that: The molybdenum disulfide is prepared by a lithium intercalation method or a hydrothermal method.
8. The slick water fracturing fluid according to claim 1, characterized in that: Calculated by weight percentage of the slick water fracturing fluid, the slick water fracturing fluid includes 0.08-0.12 wt % of the chitosan, 0.5-0.7 wt % of the polyacrylamide hydrolyzate, 0.04-0.06 wt % of paraformaldehyde, 0.15-0.25 wt % of molybdenum disulfide and the balance of water, and the molar ratio of amide group to carboxyl group in the polyacrylamide hydrolyzate is (98-70):(10-20).
9. A method for preparing the slick water fracturing fluid according to any one of claims 1 to 8, characterized in that: The preparation method comprises: sequentially mixing chitosan, a polymer matrix, paraformaldehyde, optional molybdenum disulfide and a solvent to obtain the slick water fracturing fluid; Preferably, hydrochloric acid is added during the mixing process of the chitosan and the solvent to adjust the pH to 2-7.
10. Use of the slick water fracturing fluid according to any one of claims 1 to 8, or the slick water fracturing fluid prepared by the preparation method of the slick water fracturing fluid according to claim 9, in the field of oil and gas field development.
Citation Information
Cited By
Chitosan molybdenum disulfide nano blocking agent and water-based drilling fluid
CN120718611A
Polyacrylamide thickening agent for fracturing and preparation method thereof
CN122302861A
A polyacrylamide-based thickening agent for fracturing and a preparation method thereof
CN122302861B